Composing the Synthetic Defense Index. Some Methodological Notes on Constructing the Measure for Determining the Strength of Antitakeover Charter Provisions Composition - Szymanski, Marek (Экономика и банки, 2017)
В статье рассмотрены некоторые методологические проблемы, связанные с вычислительной основой синтетического метода измерения защищенности компании от недружественного поглощения. Такой метод может быть полезным для дальнейших исследований, касающихся финансовых последствий введения, удаления или изменения противопоглотительных мер в Уставе компании. Традиционно используемые методы не учитывают особенности систем права стран и не учитывают некоторые теоретические ограничения. С учетом этих недостатков приводятся предложения с целью достигнуть «правильных» значений показателей. Ключевые слова: методологические проблемы, финансовые последствия, Устав компании, синтетический индекс защиты, поглощение. This paper presents some methodological problems with computing sole, synthetic measure of company’s safeguard against the hostile takeover. Such a measure could be useful in further researches concerning financial effects of introducing, removing or existing of antitakeover charter provisions. Commonly used measures suffer for inadequacy to other countries law systems and for disregarding some theoretical constraints. From these weaknesses the general proposals on how to design the “right” index results. Key words: shark repellents; technical barriers to takeover; antitakeover charter provisions, synthetic defense index; hostile takeovers; publicly traded companies.